Avirulent isolates of Corynebacterium fascians that are unable to utilize agmatine and proline. - Sabart, P R (1986)
Growth of a highly virulent strain of the phytopathogen Corynebacterium fascians on rich media at 37 degrees C resulted in a loss of virulence in a majority of the population within 10 generations. Strains retained virulence during cultivation at 30 degrees C on a minimal medium with ammonia as a nitrogen source. Populations of avirulent strains on the surfaces of pea seedlings decreased, whereas the number of cells of the virulent strain increased 1,000-fold during a 3-week period. All avirulent mutants isolated by growth on rich media at 37 degrees C were unable to grow on media containing agmatine or proline as sole sources of nitrogen. The ability of the mutants to grow on pea seedlings and cause fasciation disease appeared to be related to their ability to utilize nitrogen sources available on plant surfaces.